2015
DOI: 10.1007/s00429-015-1061-4
|View full text |Cite
|
Sign up to set email alerts
|

Individual variation in the neural processes of motor decisions in the stop signal task: the influence of novelty seeking and harm avoidance personality traits

Abstract: Personality traits contribute to variation in human behavior, including the propensity to take risk. Extant work targeted risk-taking processes with an explicit manipulation of reward, but it remains unclear whether personality traits influence simple decisions such as speeded versus delayed responses during cognitive control. We explored this issue in an fMRI study of the stop signal task, in which participants varied in response time trial by trial, speeding up and risking a stop error or slowing down to avo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 93 publications
(103 reference statements)
0
8
0
Order By: Relevance
“…Next, 8 min of resting-state fMRI data were collected. After completion of resting state fMRI scan, participants were engaged in 3 sessions of stop signal task (SST) ( Hu et al, 2016 ), the results of which are reported elsewhere. After each session of SST (T4, T5, and T6), saliva samples and affect ratings were collected.…”
Section: Methodsmentioning
confidence: 99%
“…Next, 8 min of resting-state fMRI data were collected. After completion of resting state fMRI scan, participants were engaged in 3 sessions of stop signal task (SST) ( Hu et al, 2016 ), the results of which are reported elsewhere. After each session of SST (T4, T5, and T6), saliva samples and affect ratings were collected.…”
Section: Methodsmentioning
confidence: 99%
“…Areas showing higher activation in women included bilateral cerebellum, thalamus in the region of the habenula, dorsomedial prefrontal cortex in the supplementary motor area, left posterior SFG, bilateral putamen, and right anterior insula. While we would not attempt to offer a post hoc account of the sex differences in these areal activations, it seems that, for both responses to reward and to punishment, men engage areas supporting memory, visual attention and self-control ( Hu et al. 2016 ) whereas women engage the saliency circuit, including the thalamus and insula, to a greater extent ( Hendrick et al.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been suggested that the inter-individual variability in response to hearing music and music preference may be influenced by temperament traits (Gerra et al, 1998 ; Nater et al, 2005 ). NS had also been associated with speeded motor responses (risk-taking) (Forstmann et al, 2008 ; Hu et al, 2016 ). In line with this, an influence through preconceptual bias in perceptual memory and habit formation is a proposed mechanism of temperaments (Cloninger et al, 1993 ).…”
Section: Discussionmentioning
confidence: 99%